2014
DOI: 10.1186/s13048-014-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary interleukin-1β levels among gynecological patients

Abstract: BackgroundEarly detection of epithelial ovarian cancer (OC) is necessary to overcome the high mortality rate of late stage diagnosis; and, examining the molecular changes that occur at early disease onset may provide new strategies for OC detection. Since the deregulation of inflammatory mediators can contribute to OC development, the purpose of this pilot study was to determine whether elevated urinary levels of Interleukin-1beta (IL-1 beta) are associated with OC and associated clinical parameters.MethodsUri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Elevated levels of IL-6 have been found in the serum and ascites of OC patients [ 71 ] and are also associated with poor prognosis [ 2 ]. In support of the data reported herein, we recently found that urinary levels of IL-1 β were generally 5 times greater in women with OC compared to healthy controls [ 72 ]. Interestingly, while exact BRCA1 mutational status could not be determined, we also found that urinary levels of IL-1 β were 3 times higher among women with benign ovarian disease and a FH of breast/ovarian cancer compared with women with benign ovarian disease and lacking a FH of breast/ovarian cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated levels of IL-6 have been found in the serum and ascites of OC patients [ 71 ] and are also associated with poor prognosis [ 2 ]. In support of the data reported herein, we recently found that urinary levels of IL-1 β were generally 5 times greater in women with OC compared to healthy controls [ 72 ]. Interestingly, while exact BRCA1 mutational status could not be determined, we also found that urinary levels of IL-1 β were 3 times higher among women with benign ovarian disease and a FH of breast/ovarian cancer compared with women with benign ovarian disease and lacking a FH of breast/ovarian cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Twelve studies explored the diagnostic and predictive potential of proteins and metabolites in urine for OC 64‐75 . Four studies show the potential of DNA methylation profiles, miRNA expression and exosomes in urine for detection 76‐79 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies explored the diagnostic and predictive potential of proteins and metabolites in urine for OC. [64][65][66][67][68][69][70][71][72][73][74][75] Four studies show the potential of DNA methylation profiles, miRNA expression and exosomes in urine for detection. [76][77][78][79] Although all these studies showed good performance, almost none specified which urine fraction or preservation method, if any, they used.…”
Section: Ovarian Cancermentioning
confidence: 99%